2016
DOI: 10.1016/j.bone.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fractures in the United Kingdom 1988–2012: Variation with age, sex, geography, ethnicity and socioeconomic status

Abstract: Summary-Rates of fracture worldwide are changing. Using the Clinical Practice Research Datalink (CPRD), age, and gender, geographical, ethnic and socioeconomic trends in fracture rates across the United Kingdom were studied over a 24 year period 1988-2012. Previously observed patterns in fracture incidence by age and fracture site were evident. New data on the influence of geographic location, ethnic group and socioeconomic status were obtained.Introduction-With secular changes in age-and sex-specific fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
261
4
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(295 citation statements)
references
References 47 publications
17
261
4
13
Order By: Relevance
“…These data are summarised in the table below, and clearly demonstrate that the differences in fracture incidence by ethnicity are congruent with the raw incidence data presented in our paper, with rates highest in whites, intermediate in South Asians and lowest in blacks. In conclusion, whilst there are ethnic differences in age distribution in the UK, these do not explain the differential fracture rates; as discussed in our paper [1], variations in factors such as BMD, bone geometry and Correspondence and reprint requests to: Professor Cyrus Cooper, …”
mentioning
confidence: 53%
See 2 more Smart Citations
“…These data are summarised in the table below, and clearly demonstrate that the differences in fracture incidence by ethnicity are congruent with the raw incidence data presented in our paper, with rates highest in whites, intermediate in South Asians and lowest in blacks. In conclusion, whilst there are ethnic differences in age distribution in the UK, these do not explain the differential fracture rates; as discussed in our paper [1], variations in factors such as BMD, bone geometry and Correspondence and reprint requests to: Professor Cyrus Cooper, …”
mentioning
confidence: 53%
“…
We recently demonstrated differences in fracture incidence by ethnicity in the UK population using the Clinical Practice Research Datalink (CPRD) [1]. In their letter, Harper et al [2] draw attention to the differential age structure of the UK population by ethnicity, and suggest that the lower incidence of fractures in Asian adults over 50 years might reflect the lower proportion of very elderly individuals within this demographic compared with the white population.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with common fragility fractures such as hip and distal radius, which have a higher incidence in women [8]. Furthermore, the same Ferguson et al [3] showed that in the elderly there was an increased preponderance of anterior column fractures, anterior wall and anterior column and posterior wall secured at a transverse as to young adults.…”
Section: Discussionmentioning
confidence: 96%
“…In the older adult, osteoporosis and poor postural stability are associated with these fractures after falls onto an outstretched hand [1,[6][7][8]9•]. Distal radius fracture in young patients usually occurs in the setting of play or sports and accounts for 23% of all sports-related fractures in adolescents [10].…”
Section: Introductionmentioning
confidence: 99%